Kontra Ideologi Terorisme Menurut Nahdlatul Ulama dan Muhammadiyah di Lamongan - Fakhruddin, M. Anas (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
This article explained how the two major organizations Muhammadiyah and Nahdlatul Ulama addressing steps fundamentalist groups in Lamongan. Muhammadiyah change the pattern of motion to promote and conduct large-scale reproduction for the muballigh. Muhammadiyah accommodated in preachers bank. And expanding missionary that has been more advanced aspects of speech to the missionary movement that led to the context aspect, which contains the values ??of action. While NU through Nahdliyah fikrah principle has five characteristics, namely: 1). Moderate, 2). Tolerant, 3). Reformative 4). Dynamic 5). Methodological mindset. Both organizations have equal society in terms of doing routine for Improving the quality of the religious with the aim of fortifying the community of Islam to understand the influence of non Ahlus Sunnah wal Jama'ah